Legitimasi Kedudukan Qanun Jinayah Aceh dalam Sistem Hukum Nasional: Analisis Peluang Penerapan di Daerah Lain - Zaky Anggara; Sopi Laeli Fitri Rahmawati; Sita Jahrotun Nisa; Deden Najmudin (Al'Adalah, 2025)
Optimism regarding the integration of Islamic criminal law based on Aceh's success as a national legal laboratory shows optimism regarding the integration of Islamic criminal law in other provinces. Ideally, the Qanun Jinayah creates humanistic and constitutional justice, but in practice it still faces legal disharmony in the socio-political sphere. This study uses a qualitative method with a normative juridical approach through a statute approach and conceptual approach. Data was obtained through a literature study of primary sources such as Law No. 11 of 2006, Qanun Aceh No. 6 of 2014, and Aceh Governor Regulation No. 5 of 2018, as well as secondary data in the form of academic literature and scientific journals. The analysis was conducted descriptively and analytically through content analysis to identify the normative position of the Qanun Jinayah, potential legal disharmony, and opportunities for applying its legal values outside Aceh. This study presents a novelty by placing the Qanun Jinayah Aceh as a model for the integration of Sharia law into national law through analysis that is not only normative but also sociological and political. Thus, several recommendations from this study are the strengthening of national law integration, the reformulation of the approach to Islamic criminal law, and the critique of the challenges of enforcing Qanun in other regions to demonstrate the opportunities for applying the Qanun Jinayah Aceh in Indonesia.